Effect of Intra Umbilical Vein (IUV) Injection of Oxytocic Agents on Outcome of the Third Stage of Labor: A Meta-analysis. - Kumar Bishnoi, Ravin; Devi, Shivani; Desai, Shrikant (International Journal of Nursing Research, 2023)
Background: Active management of the third stage of labor can easily prevent life-threatening complications of the third stage such as retention of the placenta or its parts, prolonged duration, or postpartum hemorrhage due to atonicity of the uterus. Intraumbilical vein (IUV) injection of oxytocic agents is recommended by some guidelines. Unfortunately, intravenous (IV) oxytocin, although common practice, has not been compared with IUV oxytocic agents in reviews and meta-analysis. Therefore, the main objective of this meta-analysis was to compare the effects of IUV oxytocic agents with intramuscular (IM) and Intravenous (IV) oxytocics on outcomes of the third stage. Materials and Methods: The authors searched randomized and non-randomized control trials through electronic databases which include PubMed, Cochrane Library, and CINAHL and gray literature. The search terms were “umbilical vein injection,” “intraumbilical vein injection,” “umbilical vein oxytocin,” oxytocin, uterotonic, placenta, “retained placenta,” labor, “third stage of labor,” and “postpartum hemorrhage.” Five hundred and ninety-four articles were identified and nine met the inclusion criteria. Data were analyzed by Review Manager 5.3. Results: The pooled results reported that duration of the third stage was 1.23 minutes (95% confidence interval [CI]: 0.41–2.04) shorter, amount of blood loss was 79.09 ml. (95% CI: 46.90–111.28) lesser, and placental separation time was 37.69 seconds (95% CI: 0.58–74.80) shorter in the IUV oxytocin group than the IV oxytocin group. Comparison of IUV oxytocin and IV carbetocin shows no statistically significant differences. In comparison with IM oxytocin, IUV oxytocin also results in 1.13 min (95% CI: 0.28–1.97) shorter duration of the third stage of labor but not shows any significant difference for amount of blood loss. Conclusion: IUV oxytocin is more beneficial for reduction of duration of the third stage of labor, amount of blood loss, and placental separation time than the IV and IM oxytocin.